Adipose tissue insulin resistance in young Japanese women is associated with metabolic abnormalities and dehydroepiandrosterone-sulfate - Sato, Motonori; Tamura, Yoshifumi; Kaga, Hideyoshi; Yamasaki, Nozomu; Kadowaki, Satoshi; Sugimoto, Daisuke; Nakagata, Takashi; Someya, Yuki; Nishida, Yuya; Kawamori, Ryuzo; Watada, Hirotaka (Frontiers in Endocrinology, 2024)
The proportion of young Japanese women who are underweight is exceptionally high. We previously showed that the prevalence of impaired glucose tolerance (IGT) was high in underweight young Japanese women, and that IGT was characterized by high free fatty acid levels and adipose tissue insulin resistance (ATIR).As the next step, this study aimed to explore factors associated with elevated ATIR in this population.Participants: Ninety-eight young, healthy, underweight women participated in this study.To investigate the relationship between ATIR and metabolic parameters, participants were divided into three groups (Low, Medium, and High) according to ATIR level. Body composition examination, oral glucose tolerance testing, and blood biochemical analysis were performed; Adipo-IR and the Matsuda index were used as indices of ATIR and systemic insulin sensitivity, respectively.Results: Participants in the High ATIR group had the highest prevalence of IGT (25%), and significantly higher body fat percentage, whole-body insulin resistance, and levels of insulin-like growth factor-1 and dehydroepiandrosterone sulfate (DHEA-S) than the other two groups. They were also significantly younger and had higher systolic blood pressure than the Low ATIR group. Multiple regression analysis showed that DHEA-S, which is known to enhance lipolysis in adipose tissue, was an independent correlate of ATIR.Conclusions: Underweight Japanese women with high ATIR had impaired metabolism, a higher prevalence of IGT, higher systemic insulin resistance, and higher systolic blood pressure. DHEA-S was a determinant of high ATIR levels.